2020
DOI: 10.1126/sciadv.abe6393
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar cells in Pacinian and Meissner corpuscles are touch sensors

Abstract: The skin covering the human palm and other specialized tactile organs contains a high density of mechanosensory corpuscles tuned to detect transient pressure and vibration. These corpuscles comprise a sensory afferent neuron surrounded by lamellar cells. The neuronal afferent is thought to be the mechanical sensor, whereas the function of lamellar cells is unknown. We show that lamellar cells within Meissner and Pacinian corpuscles detect tactile stimuli. We develop a preparation of bill skin from tactile-spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 52 publications
7
56
0
Order By: Relevance
“…2). Despite functional diversity of sensory Schwann cells they possess one common feature which is their selective involvement in the transduction of mechanical stimuli, a feature that appears to be evolutionarily conserved 27 . Thus, we show that polymodal nociceptors require nociceptor Schwann cells for their mechanosensitivity, but not thermosensitivity.…”
mentioning
confidence: 99%
“…2). Despite functional diversity of sensory Schwann cells they possess one common feature which is their selective involvement in the transduction of mechanical stimuli, a feature that appears to be evolutionarily conserved 27 . Thus, we show that polymodal nociceptors require nociceptor Schwann cells for their mechanosensitivity, but not thermosensitivity.…”
mentioning
confidence: 99%
“…Thus, recently identified specialized Schwann cells that surround the peripheral endings of unmyelinated nociceptors may directly participate in the detection of noxious mechanical stimuli (Abdo et al, 2019). In addition, cells that form specialized sensory end-organs innervated by mechanoreceptors in birds were also recently shown to be mechanosensitive (Nikolaev et al, 2020). Using our global Tmem150c -/- mutant mice we wished to test whether loss of the TMEM150c protein had an impact on the mechanosensitive properties on functionally identified sensory neurons using ex vivo skin nerve preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all TRP (transient receptor potential) families of ion channels have members with potential mechanosensory capacities ( Clapham et al, 2005 ; Samanta et al, 2018 ). Nevertheless, it has not been established whether these ion channels are mechanosensors or participate only when required for mechanosensation since some of them are insensitive to membrane stretch [see ( Nikolaev et al, 2020 )]. As far as we know, TRPV4 (vanilloid 4) is the only member of the TRP superfamily that has been detected in the lamellar cells of human digital Meissner ( Alonso-González et al, 2016 ).…”
Section: The Role Of the Lamellar Cells In Mechanotransductionmentioning
confidence: 99%
“…The most overwhelming putative role of lamellar cells in mechanosensation was provided recently by Nikolaev et al (2020) . They observed that the lamellar cells of Grandry’s corpuscles (assimilated to the lamellar cells within Meissner corpuscles) from duck bill skin detect tactile stimuli, thus, suggesting that also lamellar cells are touch sensors.…”
Section: The Role Of the Lamellar Cells In Mechanotransductionmentioning
confidence: 99%